Correlation Between Carbon Monoxide Level In Exhaled Air and Pulmonary Function On Grill Street-Vendors In Medan City - Chen, Jery; Noni Novisari Soeroso; Syamsul Bihar; Lambok Siahaan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2021)
Background. Air pollution is the result of household waste responsible for 3.8 million death and 7.7% of all mortality over the world. One air pollutant which tends to increase year by year is carbon monoxide (CO). CO is produced as the result of the imperfect combustion of machines and the combustion of charcoal. The purpose of this study is to assess the correlation between CO level in exhaled air and pulmonary function on grill street-vendors in Medan city. Method: This study is an observational analytic with a cross-sectional approach. The subjects were grill in Medan city who fulfilled certain inclusion and exclusion criteria with the consecutive sampling method. This study data is primary data which is collected using a questionnaire, smokerlyzer, and spirometry. Result: The subjects of this study are 25 grill street-vendors. Most subjects in this study have red (40%) and green (32%) zone in CO exhaled test and as in pulmonary function test, restrictive (56%) and mixed-type (40%) are the most. The Spearman correlation result between CO level in exhaled air and pulmonary functionÂ  FEV1 and FVC are not significant (p=0.068 and p=0.251). Conclusion: There is no significant correlation between CO levels in exhaled air and pulmonary function